Establishment of transformation protocol and regeneration potential comparison following introduction of the antiporter gene in peanut (Arachis hypogaea L.) - Khan, Kashmery (BRAC University, 2015)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology